2020
DOI: 10.3389/fphys.2020.574371
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Prospects in the Research of Nascent Adhesions

Abstract: Nascent adhesions are submicron transient structures promoting the early adhesion of cells to the extracellular matrix. Nascent adhesions typically consist of several tens of integrins, and serve as platforms for the recruitment and activation of proteins to build mature focal adhesions. They are also associated with early stage signaling and the mechanoresponse. Despite their crucial role in sampling the local extracellular matrix, very little is known about the mechanism of their formation. Consequently, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 189 publications
1
17
0
Order By: Relevance
“…α5β1 integrin binding to fibronectin could initiate fibronectin fibrillogenesis or focal adhesion formation in the immediate area, further stabilizing the filopodia (Singh et al, 2010). The discrete areas of α5β1 integrin along the shaft may indicate nascent adhesions (Henning Stumpf et al, 2020). This agrees with the 2-step theory of filopodial elongation, where integrins transiently engage the substrate to stabilize it while additional components are transported toward the tip by Myo10 (He et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…α5β1 integrin binding to fibronectin could initiate fibronectin fibrillogenesis or focal adhesion formation in the immediate area, further stabilizing the filopodia (Singh et al, 2010). The discrete areas of α5β1 integrin along the shaft may indicate nascent adhesions (Henning Stumpf et al, 2020). This agrees with the 2-step theory of filopodial elongation, where integrins transiently engage the substrate to stabilize it while additional components are transported toward the tip by Myo10 (He et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…Our immunostaining data suggest that Myo10 may traffic αvβ3 integrin to the filopodia tip, like its role for β1 integrin. Also, αvβ3 integrin may be involved in transiently binding to ECM substrates in nascent adhesions in the filopodial shaft and tip (Henning Stumpf et al, 2020). Our prior live imaging studies showed that filopodial tips are cleaved, which allows the filopodia to retract back toward the cell (Keller and Kopczynski, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The current view of integrin activation and focal adhesion assembly, based largely on studies in fibroblasts, is that mechanosensitive proteins kindlin2 and talin1 bind to and stabilize active integrins, allowing engagement with rearward flowing actin, recruiting vinculin and opening additional binding sites to build the adhesion and generate high ECM traction force (Henning Stumpf et al, 2020, Kanchanawong et al, 2010, Legerstee et al, 2021, Wolfenson et al, 2019, Zhu et al, 2021). The structural components of focal adhesions are recruited in a timespan of a few seconds (Bachir et al, 2014, Choi et al, 2008, Han et al, 2021, Laukaitis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when the GXXXG-motif was mutated to GXXXI, which is known to abrogate dimerization, an αvβ3 variant was generated that displayed dissociated transmembrane domains, exhibiting high-affinity and constitutively active signaling competence [ 76 ]. This allows the re-association of the separated subunits to form homooligomers (dimers in the α-subunit and trimers of the β-subunits) with new RGD binding pockets [ 85 , 86 ], which can further bind to other proteins to form nascent adhesions ( Figure 2 ) [ 20 , 62 , 69 , 70 , 71 , 81 , 87 , 88 , 89 ]. Subsequently, upon multiprotein clustering, focal adhesions are formed, which are the sites where integrin signaling takes place [ 62 , 68 , 69 , 70 , 71 , 88 , 90 ].…”
Section: Integrin/ecm Cell Adhesion and Signaling Receptorsmentioning
confidence: 99%